(untitled) (De Musica, 2021)
Musical works are systems regulated by feedback and feedforward mechanisms, linking social actors with their cultural and technological context. Meaning and relevance of a musical work are determined by its level of organization along with its aesthetic quality, but its survival relies on the interplay between social and technological actors, who can accomplish some state transitions allowing to maintain the balance of the work during its passages through different media environments and contexts. Nowadays, mediations, abstraction levels and new cultural archives coded in the web, produce a gap between development and culture, between invisible digital processes and perceptible cultural realities, creating new forms of emergence and selection. The responsibility of the publisher is to maintain the system of the work at a low entropic level while preserving its constitutive complexity. This presentation showcases some examples of restitution of electronics and mixed musical works and analyzes the transition of a representative model between different technological contexts.